Teaching experiences at university level in the context of online education imposed by the COVID-19 pandemic (Itinerarios Educativos, 2021)
University education is not aimed at merely transferring knowledge but rather training professionals who can provide answers to the problems that arise in current societies. The teaching process and its didactic configurations (selection of contents, communication strategies, resources, methodological construction, teacher-student relationship) undergo a constant redefinition process to attain the appropriate training objectives. The aim of this paper is to share teaching experiences when facing the adaptations and changes in didactic configurations for university courses as a result of the Covid-19 pandemic and the consequent need for pedagogical continuity in virtual environments. Teaching practices became an object of reflection and knowledge production intended to improve educational quality taking into account students’ assessment of the process towards what emerged to be the new normal in education
Keywords: didactics of geography; didactic configurations; didactic strategies; virtualization of higher education